Coagglutination for viral DNA preparation of canine parvovirus for molecular diagnosis - Mendes Ribeiro, Marcela Cristina [UNESP]; Araujo, Joao Pessoa [UNESP] (Elsevier B.V., 2009)
The use of PCR for molecular diagnosis is accepted as the standard method for detecting nucleic acids from numerous major infectious agents using diverse sampling techniques. Although PCR is an essential tool in the research laboratory; the success of the method depends on a sample free of inhibitors that was obtained preferably by a simple and fast extraction method. The coagglutination test (COA test) is based on the propriety of protein A, from Staphylococcus aureus, which can bind specifically to the Fc portion of immunoglobulin G (IgG) in various mammals and to several IgG subclasses in mice. In this study, the COA method capacity of generating inhibitor-free DNA sample was tested. Ten fecal samples positive for canine parvovirus were subjected to nucleic acid extraction using COA method and a commercial kit (Illustra (TM) GFX (TM) Genomic Blood DNA Purification Kit/G.E. Healthcare); and the samples' viral DNA content were compared using real-time PCR. The COA procedure allowed the extraction of larger amount of viral DNA from feces than the commercial kit. This method was shown to be simple and effective for DNA extraction, concentrating viral particles dispersed in the biological samples. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Staphylococcus aureus; Coagglutination; Virus; DNA; Molecular diagnosis